Transformational Leadership and Mentoring: A Panacea for Capacity Building - Bodilenyane, K.; Mooketsane, K. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
The importance of capacity building in organisations cannot be overemphasised. The realities of the working place have increased the need for organisations to find ways of improving efficiency and effectiveness. Scholars have identified a number of measures for capacity building, and one such measure is mentoring and coaching. The paper focuses on mentoring and discusses behaviours and attributes relevant for successful mentoring. The paper finds transformational leadership concomitant to mentoring, hence for successful mentoring, transformational behaviours and attributes are relevant. Therefore, the paper argues that not every supervisor or leader can be a mentor, but observable transformational attributes are necessary for successful mentorship. To understand the notion of mentoring and transformational leadership, the study reviews levels of understanding leadership by Maxwell as a conceptual framework. The paper concludes that for effective mentoring, transformational leaders graduate from one level of leadership to another until they reach pinnacle level.
Article published in the 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Capacity Building; Ethical leadership; Mentoring; Leadership; Executive coaching